Social Awareness in Kim Namjoon’s Speech at the United Nations Using Textual Analyze Perspective - Abhiseka, Putri Hadeka; Meinawati, Euis; Jimmi, Jimmi; Nurdini, Rahmi Aulia; Chotimah, Chusnul (Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to discover the meaning of the social awareness value in Kim Namjoon's speech in United in 2018 through an examination of the textual aspect as part of CDA. The research uses a qualitative method that focuses on the content analysis method. The data are words, phrases or sentences that are taken from Kim Namjoon's speech. The process of collecting data is library study and document of Kim Namjoon's speech. The content analysis is an interactive model, which consists of three stages: data reduction, data presentation, and conclusion drawing. The results of the study show that Kim Namjoon expressed his thoughts revealed strong moral values that encourage empathy, self-acceptance, and awareness of others. The result of the study shows that Kim Namjoon's frequent use of personal pronouns such as